2012
DOI: 10.3858/emm.2012.44.9.062
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of mouse brown adipocyte differentiation by second-generation antipsychotics

Abstract: Brown adipose tissue is specialized to burn lipids for thermogenesis and energy expenditure. Second-generation antipsychotics (SGA) are the most commonly used drugs for schizophrenia with several advantages over first-line drugs, however, it can cause clinically-significant weight gain. To reveal the involvement of brown adipocytes in SGA-induced weight gain, we compared the effect of clozapine, quetiapine, and ziprasidone, SGA with different propensities to induce weight gain, on the differentiation and the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…In BAT, our gene expression data showed that olanzapine treatment significantly decreased the expression of ten adipogenic or lipogenic genes, without up-regulation of genes involved in lipid metabolism. This is consistent with a recent report from another research group stating that second generation antipsychotics inhibited the expression of a number of adipogenic and lipogenic genes [60]. Our results also showed that the addition of either metformin or berberine restored the expression of eight of these ten genes to near normal levels.…”
Section: Discussionsupporting
confidence: 93%
“…In BAT, our gene expression data showed that olanzapine treatment significantly decreased the expression of ten adipogenic or lipogenic genes, without up-regulation of genes involved in lipid metabolism. This is consistent with a recent report from another research group stating that second generation antipsychotics inhibited the expression of a number of adipogenic and lipogenic genes [60]. Our results also showed that the addition of either metformin or berberine restored the expression of eight of these ten genes to near normal levels.…”
Section: Discussionsupporting
confidence: 93%
“…The administration of the drug at 20-fold higher concentration than the upper limit of therapeutic reference range resulted in a significant inhibition of the differentiation of a murine brown preadipocyte cell line. 71 However, toxic effects of the treatment for the cultured cells cannot be excluded at this high clozapine concentration. 47 On the other hand, clozapine administration at the concentrations of therapeutic reference range had a slight positive effect on the expression of the selected BAT marker genes in an in vitro mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…A study showed that Clozapine (40 µM) inhibited resistin mRNA expression in mouse brown adipocytes (76). However, in 121 schizophrenia patients treated with clozapine (403 mg/day), high serum levels of resistin were associated with smokers in comparison with non-smokers (77).…”
Section: Clozapinementioning
confidence: 96%